Fractal Rhythm In Local Architectural facades - Enas S. Abed El Ahaad; Venus Suleiman (Iraqi Journal of Architecture and Planning, 1970)
"The research focuses on local architectural facades in Baghdad and the chaos and confusion ,Loosing the balance and order that these facades suffered from, due to random and irresponsible architectural practices, with the emergence of the idea of fractional rhythm as a regulatory tool achieves that exciting balance back between the extremes (contextual and disorder), the research problem has Defined that there is no study diagnosed this confusion and anarchy in local architectural facades in Baghdad based on the idea of fractional rhythm, on that base the research's goal is to Identify practical procedures to reach to facades with fractional rhythm far from the anarchism and confusing, to enrich back our local facades. To achieve research's goal, a methodology has been determined to formulate a theoretical framework for fractal rhythm which Sets fractional rhythm indicators and detailed variables through reviewing studies and establishing a sufficient knowledge base to apply the abstract framework within an exploratory study on Samples of elevations belong to local architectural heritage To examine the grade of diversity and identify mechanisms adopted and the design characteristics (formal and substantive), that achieved the distribution of fractional rhythm reaching to test these results on the two sets of contemporary facades the first based on local heritage as Primary source of design when the second is random design to support the results derived and Provide The final conclusions of the research that provides treatment solutions to this disordered and chaotic reality in our contemporary local facades."